Planejamento conservacionista em estradas não pavimentadas em escala de bacia hidrográfica - Silva, Cristiano Carvalho da (2019)
On a catchment scale, beyond land use and soil management, unpaved rural roads take an important role on controlling erosive processes on hillslopes and drainage network, processes which are amplified by its inadequate allocation and management. The solutions for runoff managing in unpaved rural roads focus mainly on its storage in detention and retention pounds and/or conduction to infiltration terraces. However, few studies address conditions of shallow and steep soils, which hinder the storage of surface runoff, in addition to choosing the best route to runoff regulation. To this end, the techniques of monitoring and modelling erosive and hydrological processes on a catchment scale is used as one of the strategies for choosing the most effective and least costly conservationist practices, optimizing management’s financial resources. Runoff and sediment yield reflect changes in land use, as well soil and water management practices, including the unpaved roads. Given this, the aim of this study is to comprehend the impact of conservationist practices on unpaved roads and its effect on the hydrological and erosive dynamic on the scale of a small order catchment. For this purpose, a study took place on the experimental catchment of stream Lajeado Ferreira in Arvorezinha – RS, combining monitoring and mathematical modeling techniques. We calibrated LISEM (Limburg Soil Erosion Model) model with eight rainfall events with water discharge and suspended sediment concentration data from the years 2014 to 2017. From that, three conservationist scenarios were created: low (BI), medium (MI) and high (AI) intervention. BI represents more cost-efficient practices comprehending dry creek bed and diversion weirs along the roads. On MI, besides the pervious practices, there are spillways grass for channel road protection to conduct the runoff until the stream. On AI were added grass strips on cropfields that contribute with runoff to roads in addition to the MI practices. The runoff reduced 17% on BI to 307% on AI. Peak flow varied from +0,9% on BI to -320,3% on AI. Sediment yield varied from +9,4% on BI scenarios to -847,8% on AI. Results obtained from the scenarios show that, through monitoring and modeling, it is possible to investigate the hydrological and erosive behavior of roads on a catchment scale and that monitoring combined to modeling allowed evaluating the scenario’s efficiency.